Large margin classifications and their applications in computer vision - Li, Xuchun (2008)
The concept of large margin classification is used as a principle for analyzing many different algorithms, such as Support Vector Machine (SVM) and Boosting. Here it is the margin instead of raw training error that is used in designing classifiers.